2019
DOI: 10.1093/scan/nsz050
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction-related changes in posterior cingulate resting brain connectivity

Abstract: Mindfulness meditation training has been shown to increase resting-state functional connectivity between nodes of the frontoparietal executive control network (dorsolateral prefrontal cortex [DLPFC]) and the default mode network (posterior cingulate cortex [PCC]). We investigated whether these effects generalized to a Mindfulness-Based Stress Reduction (MBSR) course and tested for structural and behaviorally relevant consequences of change in connectivity. Healthy, meditation-naïve adults were randomized to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 52 publications
(71 reference statements)
11
53
1
1
Order By: Relevance
“…Previous neuroimaging studies performing MBI have reported the enhanced connectivity strengths between PCC and DLPFC using the seed‐correlation analysis (King et al, 2016; Kral et al, 2019; Scult et al, 2019); however, adopting the same strategy with different seed locations, the PCC‐DLPFC connectivity strengths after MBCT were insignificantly increased in the bereaved population (Figure S2). Through a literature review, we speculated that the post‐MBI PCC‐DLPFC connectivity change is potentially influenced by the following factors, such as MBI duration, type, age, and so on.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous neuroimaging studies performing MBI have reported the enhanced connectivity strengths between PCC and DLPFC using the seed‐correlation analysis (King et al, 2016; Kral et al, 2019; Scult et al, 2019); however, adopting the same strategy with different seed locations, the PCC‐DLPFC connectivity strengths after MBCT were insignificantly increased in the bereaved population (Figure S2). Through a literature review, we speculated that the post‐MBI PCC‐DLPFC connectivity change is potentially influenced by the following factors, such as MBI duration, type, age, and so on.…”
Section: Discussionmentioning
confidence: 88%
“…This findings could be counter-intuitive because a majority of previous findings reported the reduction in emotion-induced brain activity (Huang et al, 2019;Tomasino & Fabbro, 2016) or the altered RSFC DMN (such as reduced intra-DMN and enhanced PCC-DLPFC connectivity) following the mindfulness training (Creswell et al, 2016;King et al, 2016;Zimmerman et al, 2019 (Hensley & Clayton, 2008), sleep disturbance, and neuroendocrine activations (Buckley et al, 2012). In other words, the bereavement grief could have far Previous neuroimaging studies performing MBI have reported the enhanced connectivity strengths between PCC and DLPFC using the seed-correlation analysis (King et al, 2016;Kral et al, 2019;Scult et al, 2019); however, adopting the same strategy with different seed locations, the PCC-DLPFC connectivity strengths after MBCT were insignificantly increased in the bereaved population (- ity (Zhao et al, 2019;Zimmerman et al, 2019). Therefore, the program duration and consistent practices seemed to be crucial on the connectivity enhancement.…”
Section: Mbct For Enhancing Emotion Flexibility In Brain Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Brain science has shown many different independent brain regions (Hou et al, 2020;Kral et al, 2019;Le et al, 2019;Wang et al, 2019;Leong et al, 2018;Zhang et al, 2018;Oei et al, 2018) and people can only think from one brain region at a time. Thinking from some regions like the decision-making prefrontal cortex and creative-thinking frontal cortex result in healthy and productive outcomes.…”
Section: The Eplerian Philosophymentioning
confidence: 99%
“…In behavioral and substance addictions, PCC activation has been linked to reward-related and craving processes (Kosten et al, 2006;Yao et al, 2017). For these reasons, the PCC has been proposed as a neural target for addictions, especially for meditation and mindfulness-based interventions targeting stress reduction (Brewer & Garrison, 2014;Kral et al, 2019). As we have found that measures of spirituality relate inversely to stress-related activations in largely subcortical regions including the striatum and thalamus (McClintock et al, 2019), the findings taken together suggest important roles for both cortical and subcortical processes in the beneficial effects of spirituality as well as potential neural targets in spirituality-related interventions for addictions.…”
Section: Negative Signals In the Pcc And Inferior Parietal Lobule (Ipl)mentioning
confidence: 99%